Integration of Differentiation Learning in Islamic Religious Education in Improving Spiritual Literacy in the Society Era 5.0 - Hakim, Luqmanul; Mu'id, Abdul (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
The background of this study arises from the challenges faced by Islamic Religious Education (PAI) in the Society 5.0 era, which requires integrating technology with spiritual values so that learning not only emphasizes cognitive aspects but also fosters students’ religious character. This study aims to analyze the implementation of differentiated instruction in PAI and its contribution to enhancing students’ spiritual literacy. The research employed a qualitative approach with a case study design conducted at MA YKUI Maskumambang Gresik. Data were collected through interviews, participatory observations, and documentation, and analyzed through data reduction, display, and conclusion drawing. The results show that PAI teachers applied various strategies such as peer tutoring, small groups, learning contracts, RAFT, tiering, and learning centers that accommodated students’ diverse readiness, learning styles, and interests. These strategies enhanced students’ contextual understanding of Islamic teachings and encouraged the habituation of worship and religious attitudes in daily life. The study concludes that differentiated instruction serves as an adaptive pedagogical model for Islamic education in the digital-humanistic era. Its contribution lies in reinforcing theoretical and practical foundations for developing a responsive and flexible PAI curriculum aligned with students’ needs and the demands of contemporary society.